Impact of Knowledge Management System in E-commerce Business Process: A Systematic Literature Review - Daulika, Aska; Janitradevi N., Erza; Indra Sensuse, Dana (Journal of Comprehensive Science, 2025)
Knowledge Management Systems (KMS) become increasingly important in improving business processes, notably in the E-commerce sector. This systematic literature review (SLR) investigates the implementation, impacts, and strategies solutions for KMS in E-commerce business processes. By systematically analyzing relevant literature, this paper provides insights into the diverse approaches and methodologies used for implementing KMS in E-commerce. The literature review explores the impacts of KMS implementation on various aspects of the E-commerce business process, including decision-making, innovation, customer relationship management, and organizational performance. The findings also provide valuable insights into how KMS can be effectively leveraged to improve organizational performance and competitiveness in a dynamic E-commerce environment.